2007
DOI: 10.3386/w13665
|View full text |Cite
|
Sign up to set email alerts
|

Strike Three: Umpires' Demand for Discrimination

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Judges can keep track of their sentences, outcomes of their bail hearings, and the like, to identify sources of inconsistency or bias. Research on umpires in Major League Baseball, for example, demonstrates that home-plate umpires who know their calls are being recorded and scored by machine do not express racial preferences in calling balls and strikes (in contrast to unmonitored umpires) (Parsons et al, 2011). Judges would be well advised to create such information for themselves, as major newspaper organizations today are obtaining and reporting such information.…”
Section: Resultsmentioning
confidence: 99%
“…Judges can keep track of their sentences, outcomes of their bail hearings, and the like, to identify sources of inconsistency or bias. Research on umpires in Major League Baseball, for example, demonstrates that home-plate umpires who know their calls are being recorded and scored by machine do not express racial preferences in calling balls and strikes (in contrast to unmonitored umpires) (Parsons et al, 2011). Judges would be well advised to create such information for themselves, as major newspaper organizations today are obtaining and reporting such information.…”
Section: Resultsmentioning
confidence: 99%
“…Classic research by Frank and Gilovich (1988) revealed that teams in the National Football League (NFL) and National Hockey League (NHL) whose primary jersey color was black were more likely to be penalized during the game in comparison to National Football League (NFL) and National Hockey League (NHL) teams whose primary jersey color was not black. Extant literature on baseball by Parsons, Sulaeman, Yates, and Hamermesh (2011) discovered that "pitches are slightly more likely to be called strikes when the umpire shares the race/ethnicity of the starting pitcher, an effect that is observable only when umpires' behavior is not well monitored" (p. 1,433). Novel scholarship courtesy of Price and Wolfers (2010) looked at the intersection of referee bias and skin color in basketball and found "systematic evidence of an own-race bias" (p. 1,859) that favored basketball players when they were officiated by referees of the same race.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the study conducted by Prewett-Livingston et al (1996), who find a positive effect of same-race on promotion. In sports, Parsons et al (2008) and Price and Wolfers (2007) find a same-race bias by referees in baseball and basketball respectively. The match between the gender of evaluators and candidates has also attracted attention from economists, although the empirical evidence on this respect is mixed.…”
Section: Introductionmentioning
confidence: 99%